A near-infrared and lager stocks shift xanthene-indolium sensor for probing hydrazine in mitochondria. (July 2022) - Wang, Zhiming; Liu, Qiuchen; Cai, Songtao; Liu, Chang; He, Song; Zhao, Liancheng; Zeng, Xianshun; Gong, Jin
Abstract: Hydrazine (N2 H4 ), which can disrupt the function of mitochondria and damage the morphology of mitochondria, leading to serious diseases, was classified as a restricted substance in drinking water by the U.S. Environmental Protection Agency (EPA) and the World Health Organization (WHO). In this paper, PHNN, a mitochondrial targeting probe with near-infrared emission wavelength and large Stokes shift was constructed for hydrazine detection through the expansion of the π-conjugate system, heteroatom replacement and the introduction of nitrogen positive ions. Surprisingly, the fluorescence emission wavelength of PHNN was extended to 803 nm, and the Stokes shift was widened to 158 nm, respectively. PHNN can specifically recognize hydrazine with high sensitivity with the detection limit lower than the maximum limit of hydrazine in drinking water of EPA and WHO. Importantly, the rationally designed probe PHNN could be used for imaging hydrazine in the mitochondria of living cells, providing a potential tool for further exploration of the toxicity of hydrazine to mitochondria via visualize methods. Graphical abstract: A mitochondrial targeting probe with near-infrared emission wavelength and large Stokes shift was constructed for hydrazine detection. Image 1 Highlights: We engineered a mitochondrial targeting probe with large Stokes shift for hydrazine detection. The fluorescence emission wavelength of PHNN was extended to 803 nm and the Stokes shift was widened to 158 nm. PHNN could be used for imaging hydrazine in the mitochondria of living cells.